Bulging Fontanelle and Need for Lumbar Puncture - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Etiologies of bulging fontanelle and fever and clinical evidence for lumbar puncture were determined from medical records of 153 infants treated at Assaf Harofeh Medical Center, Israel.